School well-being of Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) in Yogyakarta - Nurus Saadah (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2020)
This study aims to identify the level of schools well-being in Madrasah Aliyah (MA) and Madrasah Tsanawiyah (MTs) throughout the Special Region of Yogyakarta (DIY). This phenomenology study involved 9 Guidance Counseling (BK) teachers of 6 MTs and 7 BK teachers of 4 MA in Yogyakarta. The respondents were collected using purposive sampling and involved in Focused Group Discussion (FGD). The results showed that several schools, both Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA), have begun to recognize and implement various innovations towards school well-being. The innovations that have been carried out by some schools are as follows. In the term of loving, rolling classes were applied to reduce the students’ boredom, get them to socialize with friends, and reduce bullying. Also, to develop health, several schools collaborate with public health centre, health clinics, and the UGM Faculty of Medicine. Besides, appreciating students’ achievement, and activating parents and school forum were conducted to develop the sense of being.